Direct Torque Control (DTC) Design With Fuzzy Sugeno-Proportional Derivative for 3-Phase Induction Motor Speed Control - Ahmad Ahmad Faizal; Agustiawan Agus; Nanda Putri Miefthawati; Mulyono Mulyono; Rudy Kurniawan; Elfira Safitri; Corry Corazon Marzuki; Rahmadeni Rahmadeni (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
In general, in the industrial world, induction motors are more widely used than direct current motors, due to the characteristics of induction motors that are sturdy, reliable, easy to maintain, and relatively inexpensive. The phenomenon of changing rotational speed when the load changes results in regulation of the speed of the induction motor, which risks slow response time, there is overshoot which should still be minimized, and there are disturbances caused by external environmental factors, so that a controller is needed that is able to work effectively to optimize performance. 3 phase induction motor. The purpose of this study is to design a sugeno-PD fuzzy DTC controller, where the DTC provides a fast and strong response mounted on an AC motor. Fuzzy Sugeno provides a short calculation time and its reasoning includes wide enough data and PD to speed up the response time results. So that the proposed method produces an induction motor rotating speed according to the given setpoint of 100 rad/s with a settling time of 0.45 seconds, a rise time of 0.2 seconds and no steady state error. From the state of the plan output response before being given the controller there is a steady state error of 5 rad/s, a maximum overshoot of 5.4111%, a settling time of 0.1554 seconds and a rise time of 0.1554 seconds